PLATELET-RICH PLASMA IN VENOUS ULCER HEALING: CASE REPORT (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To evaluate the evolution of tissue repair in venous ulcers treated with platelet-rich plasma. Methods: This is a case report with the application of platelet-rich plasma for the treatment of venous ulcers in a specialized clinic in a city in the south of Minas Gerais. At each session, 20 mL of blood was collected and distributed into four tubes with sodium citrate. The blood was centrifuged to extract platelet-rich plasma. Plasma was applied to the wound after cleaning with distilled water and polyhexamethylene biguanide solution. Subsequently, the lesion was covered with gauze impregnated with petrolatum and sterile gauze as a secondary coverage, associated with elastic compression therapy. Results: Prior to therapy, the ulcer had an area of 1.18 cm2. After five weeks of treatment with platelet-rich plasma, complete healing has occurred. Conclusion: Tissue repair occurred after five weeks of treatment without any complications.